FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN CASH HOLDING PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Rahmawati, Zahrotul Auliya; Indrawati, Nur Khusniyah (Jurnal Ilmiah Mahasiswa FEB, 2014)
Cash holding is one of the most significant decisions taken by the financial managers of any food and beverages firms. The decision not only depends on the theoretical view but also the firm-specific variables. The  research  aims to test empirically the effect of Current Asset, Cash Flow, Volatility of Cash Flow, Short Term Debt, Total Debt, Leverage, Market to Book Value Ratio, Tobin’s Q, Size of Firm and Net Working Capital with Cash Holding. Population of the research are food and beverages companies. Data analysis technique uses multiple regression analysis. The results show that Short Term Debt have a  significant influence on Cash Holding and Current Asset, Cash Flow, Volatility of Cash Flow, Total Debt, Leverage, Market to Book Value Ratio, Tobin’s Q, Size of Firm and Net Working Capital have no influence on Cash Holding. Keywords : Cash Holding, Current Asset, Cash Flow, Volatility of Cash Flow, Short Term Debt, Total Debt, Leverage, Market to Book Value Ratio, Tobin’s Q, Size of Firm, Net Working Capital